Method for the characterization and quantification assessment of geological heritage adapted to Paraná State, Southern Brazil - Xavier, Fernanda Caroline Borato (2021)
Identification and evaluation of geosites are essential to the management and conservation of geological heritage. However, the only systematic geoheritage inventory done so far in a wide area of Brazil is the one in São Paulo State. In order to contribute little by little to a national systematic geoheritage inventory, this paper presents and discusses the method used in the inventory done in Paraná State. As most of the geoheritage inventory and assessment methods were developed in European contexts, it was necessary to include in the method some adjustments related to local particularities aimed at increasing the sensitivity of the method to elements of cultural value related to indigenous people and communities of former black slaves (quilombolas), as well as some ecological aspects. It is expected that the proposed method for the Paraná State can be adopted by other Brazilian states to allow a comparison of the results between the states, which is essential to cover in the future the whole country with a systematic geoheritage inventory.